2019
DOI: 10.1158/1538-7445.sabcs18-pd1-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD1-06: A phase 1b dose-escalation and expansion study of the BCL-2 inhibitor venetoclax combined with tamoxifen in ER and BCL-2–positive metastatic breast cancer (MBC)

Abstract: Background: Venetoclax, a potent and selective inhibitor of the survival protein BCL-2 (recently approved in CLL and in development in other hematopoietic malignancies), has yet to be evaluated in pts with solid tumors. BCL-2 is overexpressed in ˜85% of ER+ breast cancer. Pre-clinical findings using patient-derived xenograft breast tumor models suggest that venetoclax synergizes with endocrine therapy by increasing apoptosis. Here we report mBEP, an investigator-initiated phase 1b study of venetoclax with tamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Since then, some scholars have found that FAK may be related to Candida albicans adhesion, hyphal transformation and pathogenicity (Santoni et al., 2002). ERK 1/2 from the FAK‐MAPK pathway was significantly down‐regulated, and Bcl‐2 and other anti‐apoptotic proteins could not be activated by phosphorylation, which accelerated the apoptosis of cells (Chong et al., 2020; Lindeman et al., 2019). The expression of JNK was significantly down‐regulated, thereby inhibiting the excessive proliferation of cells (Tafesh‐Edwards and Eleftherianos, 2020; Marca and Richardson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, some scholars have found that FAK may be related to Candida albicans adhesion, hyphal transformation and pathogenicity (Santoni et al., 2002). ERK 1/2 from the FAK‐MAPK pathway was significantly down‐regulated, and Bcl‐2 and other anti‐apoptotic proteins could not be activated by phosphorylation, which accelerated the apoptosis of cells (Chong et al., 2020; Lindeman et al., 2019). The expression of JNK was significantly down‐regulated, thereby inhibiting the excessive proliferation of cells (Tafesh‐Edwards and Eleftherianos, 2020; Marca and Richardson, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether the positive results observed in diseases like CLL using anti-apoptotic inhibition will be mirrored in solid tumors, including CRC, that are commonly more difficult to treat in the clinic. Promising results have recently been reported on venetoclax when combined with tamoxifen in ER/Bcl-2-positive metastatic breast cancer with an overall response rate of 61% and a 72% clinical benefit rate 59 , which underscores the importance of testing new combination therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical data using xenograft models from ER+ breast cancer suggest that venetoclax shows a synergistic effect with tamoxifen to induce apoptosis [14]. Based on these findings, a phase 1b 3 + 3 doseescalation and expansion study was performed and presented in San Antonio [10]. The primary aim was to determine the maximum tolerated dose (MTD), define dose-limiting toxicities (DLTs) and to identify the recommended phase 2 dose (RP2D).…”
Section: Phase 1b Trial Of the Bcl-2 Inhibitor Venetoclax Combined Wimentioning
confidence: 99%